Tom e Vinícius na Alvorada: um prisma geográfico - Taoni, Lucas Jurado [UNESP] (2013)
This article has been generated by the interface between geography and music. Methodologically, we have used a multidisciplinary bibliography that contemplates cultural geography, history, music, linguistics, literature, anthropology, for we understand that, for the understanding of a polysemous code, as it is in music, we need a diversity of looks. Our main document for an analysis of the construction of Brasília is the “Sinfonia da Alvorada” (Symphony of the Dawn), composed by Antônio Carlos Jobim and Vinícius de Moraes. Here, we attempt mainly to do a textual analysis of the work under an external perspective of the symphonic work, we mean, analyzing more its semantics (considering the product between interlocution and interpretation), and less its instrumental aesthetics, although the latter is also present. Finally, we attempt to understand the connection that exists between the actors and the spaces which are metamorphosing along with the construction of the city and which puts into evidence the idea of social circularity, proposed by the “Sinfonia da Alvorada”. This piece captures social and cultural elements related to the construction of Brasília and repositions and rearranges it through the execution of the music, in such a way that this arrangement can provide a change in the senses which are constructed from the urban experience in Brasília.